A influência aguda do treinamento de resistência muscular localizada sobre os ganhos de força em mulheres moderadamente treinadas - CÂMARA, Leonardo Lucas Gama (2019)
Bodybuilding, also known as resistance training, is one of the most practiced modalities by individuals of different age groups. And there are innumerable benefits arising from the practice of bodybuilding, which includes physiological changes in various body systems. The objective of this study was to verify the acute influence of the training, which can be defined as exercises, using progressive resistance, resistance training for the female population, such as increased lean mass, fat loss of localized muscular resistance on strength gains in moderately trained women after 12 training sessions. RESULTS: Resistance training was performed in 10 female volunteers (28.5 ± 4.31 years, 61.5 ± 7.52 weight, 1.62 ± 0.05 height, 23.29 ± 1.80 BMI), with no least three months of resistance training experience. Maximum strength was assessed by the 1-RM test. The 12 session training protocol was performed with 40% of the 1RM load. Significant increases in limb strength were observed in extensor chair exercise (84.2 kg ± 4.27 pre, 86.4 kg ± 4.13 post-p <0.039) and no significant data were observed for upper limbs in the exercise (24 kg ± 1.96 pre, 24.6 kg ± 1.93 posts). We conclude that 12 sessions of localized muscle resistance training were sufficient to increase muscle strength acutely for lower limbs in moderately trained women.